2013
DOI: 10.2337/dc12-0916
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinical Symptomatic Hypoglycemia With Cardiovascular Events and Total Mortality in Type 2 Diabetes

Abstract: OBJECTIVEHypoglycemia is associated with serious health outcomes for patients treated for diabetes. However, the outcome of outpatients with type 2 diabetes who have experienced hypoglycemia episodes is largely unknown.RESEARCH DESIGN AND METHODSThe study population, derived from the National Health Insurance Research Database released by the Taiwan National Health Research Institutes during 1998–2009, comprised 77,611 patients with newly diagnosed type 2 diabetes. We designed a prospective study consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
181
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(195 citation statements)
references
References 27 publications
6
181
1
4
Order By: Relevance
“…Diabetes‐associated mortality doubled between 1990 and 2010, and after adjusting the years to reflect disability, the number of healthy years of life that were lost to this disease increased by 70% 2, 3. One of the known causes of death in patients with diabetes is hypoglycaemia 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes‐associated mortality doubled between 1990 and 2010, and after adjusting the years to reflect disability, the number of healthy years of life that were lost to this disease increased by 70% 2, 3. One of the known causes of death in patients with diabetes is hypoglycaemia 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…We screened 1273 citations and included 17 studies with a total of 1498358 participants in the meta-analysis (Bonds et al, 2010, Chiba et al, 2015, Duckworth et al, 2011, Hsu et al, 2013, Origin Trial Investigators et al, 2013, Johnston et al, 2012, Johnston et al, 2011, Khunti et al, 2015, Majumdar et al, 2013, McCoy et al, 2012, Rajpathak et al, 2015, Rathmann et al, 2013, Signorovitch et al, 2013, Zhao et al, 2012, Zoungas et al, 2010. The flow chart of the study selection in shown in the supplementary eFigure.…”
Section: Resultsmentioning
confidence: 99%
“…All studies attempted to address confounding through the use of multiple logistic regression models, and in addition three studies used Propensity Scores (Hsu et al, 2013) (Origin Trial Investigators et al, 2013, Zhao et al, 2012 .…”
Section: Confounding Factorsmentioning
confidence: 99%
See 2 more Smart Citations